2007
DOI: 10.1523/jneurosci.3583-06.2007
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Inhibition of Identified Anorexigenic POMC Neurons by Orexin/Hypocretin

Abstract: Proopiomelanocortin (POMC) neurons of the hypothalamic arcuate nucleus (ARC) suppress appetite, and lack of POMC-derived peptides or electrical silencing of POMC neurons causes obesity. ARC POMC neurons are surrounded by nerve terminals containing the wakefulness-promoting peptides orexins/hypocretins, but whether orexin affects their electrical activity has not been tested directly. Here we identify living ARC POMC cells in mouse brain slices by targeted expression of green fluorescent protein. Using whole-ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
46
7

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(60 citation statements)
references
References 39 publications
(51 reference statements)
7
46
7
Order By: Relevance
“…In other parts of the hypothalamus and brainstem, orexin excites local GABAergic interneurons to presynaptically regulate GABAergic transmission Liu et al, 2002;Eriksson et al, 2004;Ma et al, 2007). In our daytime SCN recordings, focal application of gabazine into the SCN blocked orexin's suppression of the Per1-EGFP neurons, thereby showing that orexin can increase the frequency of GABA-mediated IPSCs, presumably by increasing GABA release from local SCN neurons.…”
Section: Discussionsupporting
confidence: 50%
“…In other parts of the hypothalamus and brainstem, orexin excites local GABAergic interneurons to presynaptically regulate GABAergic transmission Liu et al, 2002;Eriksson et al, 2004;Ma et al, 2007). In our daytime SCN recordings, focal application of gabazine into the SCN blocked orexin's suppression of the Per1-EGFP neurons, thereby showing that orexin can increase the frequency of GABA-mediated IPSCs, presumably by increasing GABA release from local SCN neurons.…”
Section: Discussionsupporting
confidence: 50%
“…Fluorescent POMC-eGFP neurons were identified by epifluorescence and patched under IR-DIC optics. Whole-cell current-clamp and voltageclamp recordings were made using an EPC-9 patch-clamp amplifier, as described previously (Burdakov and Ashcroft, 2002;Plum et al, 2006;Ma et al, 2007). Patch pipettes had resistances of 3-5 M⍀ when filled with internal solution.…”
Section: Methodsmentioning
confidence: 99%
“…The peak inward current and current-voltage ( I-V) relationships were measured. Resting potentials of firing neurons were determined from slow time-scale recordings on which a clear basal line was evident; this baseline was taken as the resting potential (Plum et al, 2006;Ma et al, 2007). Fold increases in firing were determined individually for each neuron and then averaged.…”
Section: Methodsmentioning
confidence: 99%
“…The Arc receives projections densely from orexin neurons Date et al, 1999;Yamanaka et al, 2000), and Fos expression was induced in NPY neurons of the arcuate nucleus by intracerebroventricular injection of orexin, suggesting that orexinstimulated feeding may occur at least partly through NPY pathways (Yamanaka et al, 2000). Electrophysiological data showed that orexin directly and indirectly activated NPY neurons (van den Top et al, 2004; Li and 170 van den Pol, 2006) but inhibited POMC neurons (Muroya et al, 2004;Ma et al, 2007). Furthermore, the orexin A-induced increase in food intake was partly inhibited by prior administration of BIBO3304, an NPY-Y1 receptor antagonist, in a dose-dependent manner (Yamanaka et al, 2000).…”
Section: B Mechanism Of Orexin-mediated Feedingmentioning
confidence: 99%